2015
DOI: 10.1007/s00436-015-4578-9
|View full text |Cite
|
Sign up to set email alerts
|

Population identification and divergence threshold in Psoroptidae based on ribosomal ITS2 and mitochondrial COI genes

Abstract: Psoroptidae mites are a type of small mites with a wide range of hosts. The proliferation of Psoroptidae mites could cause symptoms such as severe itching, atopic dermatitis, and hair loss in infected animals. If severely infected, death can also occur. The morphological classification and identification of Psoroptidae mites is problematic due to the overlapping geographical distribution. In addition, there is no divergence threshold for molecular classification and identification. To solve this problem, gDNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Replicated sequences were removed and a total of 18 sequences were submitted to NCBI database (GenBank accession numbers: MW020108-MW020109 for T. sinensis and MW020223-MW020238 for T. ovis). The obtained 18S rRNA gene sequences in this study were aligned and analyzed with those retrieved from GenBank using ClustalW, the Muscle program in MEGA 7, and BLASTn tool of NCBI GenBank database [28][29][30]. Phylogenetic analyses were inferred by the Neighbor-Joining method based on Kimura-2 parameter model with 1000 bootstrap replicates using MEGA 7 [31][32][33][34].…”
Section: Sequencing and Phylogenetic Analysesmentioning
confidence: 99%
“…Replicated sequences were removed and a total of 18 sequences were submitted to NCBI database (GenBank accession numbers: MW020108-MW020109 for T. sinensis and MW020223-MW020238 for T. ovis). The obtained 18S rRNA gene sequences in this study were aligned and analyzed with those retrieved from GenBank using ClustalW, the Muscle program in MEGA 7, and BLASTn tool of NCBI GenBank database [28][29][30]. Phylogenetic analyses were inferred by the Neighbor-Joining method based on Kimura-2 parameter model with 1000 bootstrap replicates using MEGA 7 [31][32][33][34].…”
Section: Sequencing and Phylogenetic Analysesmentioning
confidence: 99%
“…These results were markedly different with our results, as Ma et al [37] and Shang et al [36] reported much lower effective concentrations for carvacrol and/or eugenol than in the present study. Considering that P. cuniculi and P. ovis are the same species [47], this inconsistency could be attributed to differences in the experimental design, such as the use of filter paper versus immersion and the use of different solvents. For instance, during the incubation of mites on filter paper in the study of Shang [36], the solvent (mainly water) could have evaporated, resulting in increasing concentrations of the active compound and a higher efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Due to these drawbacks, molecular techniques based on ribosomal DNA (rDNA) and cytochrome oxydase subunit 1 ( coxI ) have been used as important tools on mite identification and phylogenetic analysis (Lava Kumar et al 1999 ; Navajas and Fenton 2000 ; Vargas et al 2005 ; Ben-David et al 2007 ; De Rojas et al 2007 ; Osakabe et al 2008 ; Wong et al 2011 ; Yang et al 2011 ; Matsuda et al 2012 ; Thet-Em et al 2012 ; Arimoto et al 2013 ; Roussel et al 2013 ; Stephenson et al 2013 ; Navia et al 2014 ; Beroiz et al 2014 ; Khaing et al 2014 ; Lv et al 2014 ; Juan et al 2015 ; Li et al 2015 ; Stalažs and Moročko-Bičevska 2016 ; Peltier et al 2018 ; Syromyatnikov et al 2018 ; Zélé et al 2018 ; Zhou et al 2020 ; Gómez-Martínez et al 2020 ; Oliveira et al 2021 ; Zhang et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%